2014
DOI: 10.1007/s00122-014-2335-6
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of a dominant thermo-sensitive genic male sterility gene (BntsMs) in rapeseed (Brassica napus) with AFLP- and Brassica rapa-derived PCR markers

Abstract: A new thermo-sensitive dominant genic male sterility (TSDGMS) line of Brassica napus was found and mapped in this paper. Our result will greatly accelerate the map-based cloning of the BntsMs gene. TE5A is a thermo-sensitive dominant genic male sterility line originating from spontaneous mutation of the inbred line TE5 in Brassica napus and provides a promising system for the development of hybrid cultivars. Genetic analysis has revealed that the BntsMs mutant is controlled by a single, dominant gene. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The MS5 d gene had been previously localized to a 103-kb region that is highly syntenic to the B. rapa linkage group A8, and 24 putative genes (from Bra018439 to Bra018465 ) were identified in the target region ( Figure 1a ) (Zeng et al, 2014). Based on homolog analyses in Arabidopsis , functional annotation of the B. rapa transcripts suggested that six of the 24 B. rapa genes ( Bra018457, Bra018451, Bra018449, Bra018446, Bra018443 , and Bra018441 ) were involved in anther development 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The MS5 d gene had been previously localized to a 103-kb region that is highly syntenic to the B. rapa linkage group A8, and 24 putative genes (from Bra018439 to Bra018465 ) were identified in the target region ( Figure 1a ) (Zeng et al, 2014). Based on homolog analyses in Arabidopsis , functional annotation of the B. rapa transcripts suggested that six of the 24 B. rapa genes ( Bra018457, Bra018451, Bra018449, Bra018446, Bra018443 , and Bra018441 ) were involved in anther development 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The B. napus lines TE5A and TE5 were obtained from the Oil Crop Research Institute of the Chinese Academy of Agricultural Sciences; we described TE5A in a previous study (Zeng et al, 2014). Mutant lines were planted in a greenhouse under 25°C day/15°C night temperature conditions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations